Policy evaluation on specific allocation fund of small scale energy sector - Agnevia, Renita; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2018)
Abstract - On 2016, central government enacted a new mechanisms in Specific Allocation Fund (SAF) Policy that encourages policy complexity and existence issue, such as a delay in determining of technical guidelines. The role of MEMR on SAF policy according to Regulation of Ministry of Energy and Mineral Resources No 3/2016, states that MEMR as a Technical Ministry plays a role in monitoring and evaluation. The regulation also oblige beneficiary provinces to submit their progress reports quarterly. In fact, there are many provinces did not submit their report to MEMR. Surely this is against the rules and indicates the existence problem in monitoring and implementation process progress. The research uses qualitative approach, where the data collected in survey methods by collecting participant answer questioned administers through interviews and questionnaires. The answer from participants will describe the responses given. The question will be constructed and written properly to get reliable and valid survey. Author construct interview and design questionnaire so that participants are clear and easy to comprehend. The examine of validity data without using statistical tests, and conducted to find the meaning of research findings. Author uses triangulation to test validity data.The result showed that (1) Monitoring and Evaluation of Specific Allocation Funds on Small Scale Energy Sector is conducted by comparing the conformity of work plan with SAF's activities direction as well as conformity implementation; (2) Several causes of monitoring and evaluation problem, due to: Inexistence of standard instruction on the process of monitoring and evaluation at MEMR, Data planning have not been managed well, the regulation issue, and the absence of strict sanction; (3) Obstacles in the implementation of Specific Allocation Fund on Energy Sector Policy, include: bureaucracy, resource, communication, and disposition. While bureaucracy becomes the primary obstacles. Keywords: barriers,energy sector, implementation, MEMR, Monitoring and Evaluation, Specific Allocation Fund, policy.